Entrepreneurship education in vocational schools: an Indonesian model - Widodo, Widodo; Baswedan, Aliyah Rasyid; Suyata, Pujiati; Eka Saputra, Wahyu Nanda (Institute of Advanced Engineering and Science, 2025)
Vocational education is crucial in bridging the gap between educational outcomes and labor market demands, significantly impacting employment rates and career prospects. The purpose of the study was to identify the acceptability of the entrepreneurship education model in Indonesian vocational schools. This paper explores the importance of vocational education in equipping individuals with job-ready skills, addressing challenges like long-term unemployment, and literacy skill disparities. It emphasizes the integration of entrepreneurship education to foster entrepreneurial intentions, competencies, and behaviors, crucial for sustainable economic growth, particularly in Indonesia. Utilizing a development model based on Borg and Gall, the study involves needs assessment, product development, and evaluation to craft an effective entrepreneurship education framework for vocational schools. Insights from vocational education experts, entrepreneurship practitioners or teachers, and entrepreneurs are integral to developing this model. The findings show that entrepreneurship education is acceptable to be implemented in Indonesian vocational schools. The proposed model focuses on characteristic Indonesian mindset formation, practical entrepreneurial skills, and active industry collaboration, aiming to prepare graduates for both employment and selfemployment. This research has implications for the transformation of vocational education in Indonesia by providing a strong framework that supports graduates’ transition to the world of work and encourages entrepreneurial efforts, thereby contributing to broader economic development and innovation.